The influence of organisational culture towards employee performance at the utilities sector / Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Yusof, Raghadah; Omar Ali, Siti Rapidah; Mat, Khalid Amin (UiTM Cawangan Kedah, 2022)
The researchers focused into the impact of organisational culture on employee performance in the utilities sector. The aim of the research was to examine at the links between various factors that can influence employee performance which are employee participation, openness to communication and reward systems among employees of utilities sector. The study population, which included 134 workers working in the utilities sector, was chosen by the researchers. To gather and analyse data, a set of questionnaires was employed, which were distributed to respondents via Google Form. The researchers utilised the Statistical Package for Social Science (SPSS) version 23 to analyse the data obtained for this study. The influence of organisational on employees in this sector was determined using Correlation and Multiple Regressions analysis. The findings revealed that the independent and dependent variables have a strong correlation. The results also indicated that the three hypotheses were accepted. The researchers expected that the findings will benefit the organisation as well..